Roles of Thai Women according to the Ten Admonitions - Ueavivatsakul, konkamon (Journal of Buddhist Innovation Review, 2025)
This article aims to study the promotion of Thai women’s roles based on the Tenfold Virtuous Precepts (Owat 10 Prakan) in five key aspects: (1) Economic – emphasizing women’s roles in honest, diligent, and frugal livelihood following the principle of right livelihood (Samma-Ajiva); (2) Morality and Ethics – highlighting the observance of the Five Precepts and gratitude; (3) Social – encouraging women’s participation in building a harmonious community through loving-kindness, compassion, and equanimity; (4) Divorce and Domestic Violence – applying the principles of patience, forgiveness, and peaceful communication to reduce conflict; and (5) Child-Rearing – acknowledging women as the first teachers who instill moral values from early childhood. The study finds that adopting the Tenfold Virtuous Precepts to promote women’s roles significantly contributes to family stability, fosters a morally grounded society, and supports sustainable social development.